Risk Factors Linked to Central Catheter-Associated Thrombosis in Critically Ill Infants in the Neonatal Intensive Care Unit - Lambert, Isabella; Tarima, Sergey; Uhing, Michael; Cohen, Susan S. (American Journal of Perinatology, 2019)
Objective Our study identified risk factors for the development of clinically identifiable catheter-associated thrombosis (CT).Study Design We performed a retrospective cohort study of neonates in whom a central catheter was present. A total of 1,475 catheters were identified in 766 patients during a 36-month study period. The odds ratio (OR) of thrombi formation in catheterized neonates was modeled using simple (single predictor) and multiple (multiple predictors) logistic regressions as well as simple and multiple Cox's proportional hazard models.Result The incidence of CT was 1.17 per 100 neonates. Unadjusted factors including age at insertion, history of surgery before or during line placement, cholestasis, femoral location, and line size significantly increased the OR or hazards ratio (HR) of developing thrombi formation. In multiple logistic and Cox's regression analyses, three factors continued to be significantly associated with OR or HR of thrombi formation: line size, femoral location, and cholestasis.Conclusion We conclude that clinically identifiable CT is rare in the neonatal population. Furthermore, catheter-specific characteristics are predictive for CT and require further investigation.
Keywords: neonate; thrombosis; central catheter; neonatal intensive care unit